Sborník konference didaktiky přírodních věd DidSci+ 2021 - Bartoňová, Markéta (Masaryk University Press, 2021)
Title in English: Proceedings of the Conference on the Didactics of the Sciences DidSci+ 2021 The goal of the DidSci+ conference on the didactics of natural sciences is to enable international exchange of experience in theory and practice of teaching natural sciences. The conference is organized yearly since 2018.